Adoption in the media: review of national and international literature - Gagno, Adriana Pellanda; Weber, Lidia Natalia Dobrianskyj (Paidéia (Ribeirão Preto), 2003)
The purpose of this study was to review national and international literature about the adoption represented in media. In Brazilian literature the more relevant scientific studies are of Abreu, who deal with the genesis of the media discourse on international adoption, revealing different approaches on adoption undertaken by Brazilian and French press, the former considering international adoption as a "necessary evil", the latter as a charitable gesture towards children whose countries are unable to solve the problem of abandon; and of Gagno, who did content analysis of two nationwide Brazilian magazines, Veja and Pais & Filhos, showing that for the second, which is aimed to parents and children, family still means biological family, while for the first the topic was covered in a more diversified and broader way, maybe because the magazine is not attached to family subject. Regarding the international literature, the scanning of the PsycINFO database, in the period from 1887 to 2002, shows only one article, written by Waggenspack, which indicates the lack of public awareness on the issue and the need for more research.